Hubungan Kesehatan Mental Dengan Pencapaian Prestasi Akademik Mahasiswa Tahun Pertama di Stikes Bahrul Ulum Jombang - Laili, Hanifah Nur; Fitriyah, Erna Ts.; Roni, Faishol; Wijaya, H. Arif; Camelia, Dina (Universitas Pahlawan Tuanku Tambusai, 2024)
Student learning achievement will decrease if students experience learning difficulties related to achievement and anxiety. So someone who has a high learning intensity will tend to get good learning results. This research aims to determine the relationship between mental health and academic achievement of first year students at STIKES Bahrul Ulum Jombang. The type of research used is correlational analysis with a retrospective approach. The population in this study was all First Year STIKES Bahrul Ulum Jombang students totaling 94 students with sampling using a total sampling of 90 respondents. The research instruments used were the SRQ-29 questionnaire and the KHS score results. The statistical test in this study used the Spearman rank statistical test. The results of statistical tests using Spearman rank showed that there was a relationship between mental health and academic achievement at STIKES Bahrul Ulum Jombang with significant values ​​for anxiety and depression ρ = 0.161 > 0.05, psychotic disorders ρ = 0.569 > 0.05, and PTSD ρ = 0.761 > 0.05. He research results show that there is no relationship between mental health and the academic achievement of first year students at STIKES Bahrul Ulum Jombang. It is hoped that future researchers will carry out the same research with different samples and pay attention to the questionnaire measuring instruments that will be used.